Optimizing the Role of Universities in Empowering Early Childhood Education in Remote Areas - Azzaakiyyah, Hizbul Khootimah; Pramono, Susatyo Adhi; Siminto (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to examine strategies for optimizing the role of universities in empowering early childhood education (ECE) in remote areas through a literature review using a qualitative approach. Descriptive analysis was employed to synthesize data from 20 scholarly articles, rigorously selected from an initial pool of 40 articles retrieved via Google Scholar for the period 2016–2024. The findings reveal that universities play a strategic role in improving the quality of ECE through teacher training, development of curricula rooted in local wisdom, utilization of information technology, and collaboration with various stakeholders. Case studies from universities in Indonesia, such as Universitas Gadjah Mada and Universitas Terbuka, illustrate the success of ECE empowerment programs in remote areas. This research concludes that research-based approaches, technological innovation, and multisector partnerships can provide effective solutions to address educational challenges in remote areas. Recommendations are made for universities and governments to strengthen collaboration in developing sustainable and locally relevant ECE programs.